Temperature and adhesion influence on the microbearings operating parameters - WIERZCHOLSKI, Krzysztof. 1996 - . Politechnika Koszalińska - Instytut Technologii i Edukacji (2013)
In presented paper are elaborated the preliminary problems of thermo-hydrodynamic theory of lubrication for dependences between temperature, adhesive forces, and oil dynamic viscosity, in micro-scale inside super thin cylindrical boundary layer arising between two cooperating grooved cylindrical surfaces.
Dane z autopsji.